The chrondoprotective actions of a natural product are associated with the activation of IGF-1 production by human chondrocytes despite the presence of IL-1β - Bobrowski Paul; Ahmed Salahuddin; Miller Mark JS; Haqqi Tariq M (BMC, 2006)
Abstract Background Cartilage loss is a hallmark of arthritis and follows activation of catabolic processes concomitant with a disruption of anabolic pathways like insulin-like growth factor 1 (IGF-1). We hypothesized that two natural products of South American origin, would limit cartilage degradation by respectively suppressing catabolism and activating local IGF-1 anabolic pathways. One extract, derived from cat's claw (Uncaria guianensis, vincaria®), is a well-described inhibitor of NF-κB. The other extract, derived from the vegetable Lepidium meyenii (RNI 249), possessed an uncertain mechanism of action but with defined ethnomedical applications for fertility and vitality. Methods Human cartilage samples were procured from surgical specimens with consent, and were evaluated either as explants or as primary chondrocytes prepared after enzymatic digestion of cartilage matrix. Assessments included IGF-1 gene expression, IGF-1 production (ELISA), cartilage matrix degradation and nitric oxide (NO) production, under basal conditions and in the presence of IL-1β. Results RNI 249 enhanced basal IGF-1 mRNA levels in human chondrocytes by 2.7 fold, an effect that was further enhanced to 3.8 fold by co-administration with vincaria. Enhanced basal IGF-1 production by RNI 249 alone and together with vincaria, was confirmed in both explants and in primary chondrocytes (P <0.05). As expected, IL-1β exposure completely silenced IGF-1 production by chondrocytes. However, in the presence of IL-1β both RNI 249 and vincaria protected IGF-1 production in an additive manner (P <0.01) with the combination restoring chondrocyte IGF-1 production to normal levels. Cartilage NO production was dramatically enhanced by IL-1β. Both vincaria and RNI 249 partially attenuated NO production in an additive manner (p < 0.05). IL-1β - induced degradation of cartilage matrix was quantified as glycosaminoglycan release. Individually RNI 249 or vincaria, prevented this catabolic action of IL-1β. Conclusion The identification of agents that activate the autocrine production of IGF-1 in cartilage, even in the face of suppressive pro-inflammatory, catabolic cytokines like IL-1β, represents a novel therapeutic approach to cartilage biology. Chondroprotection associated with prevention of the catabolic events and the potential for sustained anabolic activity with this natural product suggests that it holds significant promise in the treatment of debilitating joint diseases.